What motivates students to learn about ecosystems in the socio-scientific issues classroom? - Agus Muji Santoso; Septa Adi Hendarso; Rina Yuliati; Anggi Tias Pratama; Dina Maulina; Poppy Rahmatika Primandiri; Elysabet Herawati (Biosfer: Jurnal Pendidikan Biologi, 2026)
Research on student motivation within the Socio-Scientific Issues-based ASICC model for ecosystem topics remains limited, despite its critical role in achieving deep learning principles. This study aims to uncover students' motivation to learn biology. A standard Likert-scale-based instrument was used to measure student motivation. Data were obtained from this classroom action research based on lesson study. The average student motivation scores in each cycle were compared. Then, the student motivation data was also analyzed by comparing the dimensions of motivation according to Glynn's motivation theory. The results showed a significant and consistent increase in learning motivation from the pre-cycle to the second cycle, indicating better homogeneity of motivation. This increase was also reflected in the shift in the distribution of motivation categories, where students with high and very high motivation increased. An interesting finding from this study was that students were motivated to learn by the encouragement of grades motivation. The Socio-Scientific Issues approach to biology learning was realized by implementing ecosystem learning through the ASICC learning model. Environmental issues and cases can increase student learning motivation. However, an in-depth analysis conducted in this study revealed that students' grade motivation dimension was higher than other motivational dimensions. Presenting environmental issues or cases should be able to enhance intrinsic motivation. This finding suggests that grade motivation was the most easily stimulated dimension of motivation before developing motivation in other dimensions.